Baccalaureate nursing students' experiences with high-fidelity simulation: protocol for a qualitative systematic review. Issue 12 (8th December 2020) - Zhu, Yuxuan; Geng, Cong; Pei, Xianbo; Chen, Xiaoli
Abstract : Introduction: High-fidelity simulation (HFS) can bridge the gap between theoretical knowledge and nursing practice and improve safety and quality of patient care in baccalaureate nursing education. Although inconsistent assessment instruments or lack of high-quality research designs affect the strength of the evidence and limit the generalisability of the results, quantitative studies generally demonstrate the effectiveness of HFS in baccalaureate nursing education. Synthesis of the existing evidence of baccalaureate nursing students' experiences with HFS is crucial for the improvement and revision of simulation design and teaching. Methods and analysis: A comprehensive search for qualitative studies on baccalaureate nursing students' experiences with HFS will be conducted in the following databases: PubMed, Embase, CINAHL, ProQuest, Web of Science, PsycINFO, the Cochrane library, China Biology Medicine disc, China National Knowledge Infrastructure and VIP Database for Chinese Technical Periodicals. This review considered studies reported in English or Chinese, and studies that were conducted between January 2000 and December 2019 in view of the launch of International Nursing Association for Clinical Simulation and Learning. The literature search will be conducted by two independent reviewers, and any disagreement will be adjudicated by discussion or with a third reviewer. The two independent reviewers will use the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research to assess the methodological validity, following which the JBI standardised data extraction tools will be used to extract relevant data. The JBI meta-aggregation method will be subsequently used to synthesise the data, eventually forming themes, categories and synthesised findings. The final synthesised findings will establish confidence levels based on the JBI ConQual approach. Ethics and dissemination: This review does not require formal ethical review since it is based on available published literature. Findings will be disseminated through publication in a peer-reviewed journal, and, if possible, presented in scientific conferences.